MI Dora Healing Candies / Nurafiqah Md Hussin - Md Hussin, Nurafiqah (2020)
Brief Description of the business and Product Design Mi Dora Sdn Bhd is a medicine related company that is specialized in producing medicine. It is founded by the current CEO also held the position of General Manager which are Nurafiqah Binti Md Hussin. The mission of the company is to contribute new medicine that can improve the quality of life while the vision is to provide help for all type of people. Mi Dora healing candies are the medicine invented by the company to make children easier to consume the medicine. It is a solidified liquid medicines and the shape is like dried agar- agar. Mi Dora healing candies is made from liquid medicines such as cough medicine and is added with agar-agar and sugar. After all the ingredients incorporated together, it is poured and left to dry. Then, after the mixture is dried completely it is cut into specific shapes.